Quality of life in celiac disease and the effect of gluten‐free diet. Issue 4 (6th June 2018) - C, Deepak; Berry, Neha; Vaiphei, Kim; Dhaka, Narendra; Sinha, Saroj K; Kochhar, Rakesh
Abstract : Background and Aim: Patients with celiac disease (CD) have a poor health‐related quality of life (HR‐QOL). We assessed the QOL in patients with CD using both generic (SF‐12) and specific (CD‐QOL) questionnaires, and the effect of gluten‐free diet (GFD) on HR‐QOL. Methods: We conducted a prospective follow‐up study based on consecutive patients of suspected CD between June 2014 and November 2015. After taking a detailed history, all patients were subjected to laboratory investigations (including complete blood count, biochemistry, and the IgA tTG antibody), followed by endoscopy and duodenal biopsies for histopathology. The HR‐QOL was assessed using SF‐12 and CD‐QOL questionnaires. Patients who were strictly adherent to GFD were re‐assessed at the end of 6 months for laboratory parameters and QOL. Results: Sixty adult patients of CD, with mean age of 28.85 ± 12.43 years, and a M:F ratio of 1.3:1, were enrolled in the study. The mean PCS (physical health composite scale score) and MCS (mental health composite scale score) at baseline were 37.20 ± 11.09 and 41.88 ± 8.39, which showed a statistically significant improvement after GFD to 50.30 ± 9.88 and 50.22 ± 9.04, respectively. Though there was no significant difference in the total CD‐QOL score after GFD, there was a significant improvement in the dysphoria and health‐concern subscales. We also found a negative correlation of the pre‐GFD symptom score (based on number of positive symptoms) with PCS and MCS and a positive correlation with the CD‐QOL score. Conclusion: This study has shown a reduced HR‐QOL in adult CD patients, which improves significantly on GFD, and is associated with a higher symptom number. Abstract : The study has shown a reduced health‐related quality of life in adult celiac disease patients, which improves significantly on gluten‐free diet, and is associated with higher symptom number.